(untitled) (Acta Polytechnica CTU Proceedings, 2023)
Simulations of tunnel excavations have to take into account the natural occurrence of joints and faults in the surrounding rock mass, which dominantly control its mechanical response. In this paper, we present work in progress toward 3D finite element analysis of excavation using equivalent rock-mass properties derived from stochastically generated discrete fracture networks (DFNs). The equivalent stiffness is determined by volume averaging. Presently, we solve the problem linearly for an incremental change of the stress state. The fracture’s stiffness is assumed to depend on the initial normal stress acting in direction normal to it. However, within the solved incremental step, we assume the fracture’s stiffness to be constant. This assumption is acceptable for small stress changes. Since the fractures represented in the DFN model have preferred directions, the equivalent stiffness is anisotropic.